Selective mRNA Degradation by Polynucleotide Phosphorylase in Cold Shock Adaptation in Escherichia coli - Yamanaka, Kunitoshi (American Society for Microbiology, 2001)
Upon cold shock, Escherichia coli cell growth transiently stops. During this acclimation phase, specific cold shock proteins (CSPs) are highly induced. At the end of the acclimation phase, their synthesis is reduced to new basal levels, while the non-cold shock protein synthesis is resumed, resulting in cell growth reinitiation. Here, we report that polynucleotide phosphorylase (PNPase) is required to repress CSP production at the end of the acclimation phase. A pnp mutant, upon cold shock, maintained a high level of CSPs even after 24 h. PNPase was found to be essential for selective degradation of CSP mRNAs at 15°C. In a poly(A) polymerase mutant and a CsdA RNA helicase mutant, CSP expression upon cold shock was significantly prolonged, indicating that PNPase in concert with poly(A) polymerase and CsdA RNA helicase plays a critical role in cold shock adaptation.